Students’ perspective on online learning during the COVID-19 pandemic - Irawaty Irawaty; Abdul Halim Momo; Sulfa Sulfa; Salimin Salimin; Nerlin Nerlin; Sri Yuliani Mustar (Journal of Education and Learning (EduLearn), 2022)
The COVID-19 pandemic has impacted changing the model of learning activities. Teaching and learning activities that have usually been done face-to-face have now turned into online learning. This study identified student perspectives on online learning activities for Department of Civics Education students at the Faculty of Teacher Training and Education at Halu Oleo University, Indonesia during the COVID-19 pandemic. This study used a survey method by distributing questionnaires in the form of Google Forms to students, and a total of 227 students participated in this study. Our study focused on online learning media, learning effectiveness, lecturers' abilities, obstacles, and student recommendations regarding online learning during the COVID-19 pandemic. Data analysis in this study was carried out descriptively, presented in the form of frequency, percentage, and graph. The study results found that the most effective online learning media felt by students at the Department of Civics Education were Google Meet and Zoom Cloud Meetings. Besides, the majority of students considered online learning to be no more effective than face-to-face lectures. Lecturers need to provide two-way learning materials through discussion as well as question and answer. Furthermore, the main determining factors that cause online learning to be ineffective are network constraints and internet quotas. Therefore, students expected the lecturers to understand the network constraints experienced by students during online learning and recommend implementing learning activities for blended learning (combination of online and offline) while still complying with the health protocols.